Characterization of the Wheat Leaf Metabolome during Grain Filling and under Varied N-Supply - Heyneke, Elmien; Watanabe, Mutsumi; Erban, Alexander; Duan, Guangyou; Buchner, Peter; Walther, Dirk; Kopka, Joachim; Hawkesford, Malcolm J.; Hoefgen, Rainer (Frontiers in Plant Science, 2017)
Progress in improving crop growth is an absolute goal despite the influence multifactorial components have on crop yield and quality. An Avalon x Cadenza doubled-haploid wheat mapping population was used to study the leaf metabolome of field grown wheat at weekly intervals during the time in which the canopy contributes to grain filling, i.e. from anthesis to five weeks post anthesis. Wheat was grown under four different nitrogen supplies reaching from residual soil N to a luxury over-fertilization (0, 100, 200, and 350 kg N ha-1). Four lines from a segregating doubled haploid population derived of a cross of the wheat elite cvs. Avalon and Cadenza were chosen as they showed pairwise differences in either N utilization efficiency (NUtE) or senescence timing. 108 annotated metabolites of primary metabolism and ions were determined. The analysis did not provide genotype specific markers because of a remarkable stability of the metabolome between lines. We speculate that the reason for failing to identify genotypic markers might be due to insufficient genetic diversity of the wheat parents and/or the known tendency of plants to keep metabolome homeostasis even under adverse conditions through multiple adaptations and rescue mechanism. The data, however, provided a consistent catalogue of metabolites and their respective responses to environmental and developmental factors and may bode well for future systems biology approaches, and support plant breeding and crop improvement.